Psychological factors as VO₂ max performance predictor among Malaysian sub-elite athletes - Muhammad Noor Hizami Hamidi; Shamsulariffin Samsudin; Hairul Anuar Hashim; Mohd Rozilee Wazir Norjali Wazir; Geok, Soh Kim; Roxana Dev Omar Dev (IDEAS, 2025)
This study examined the predicted correlation between certain psychological traits (emotional intelligence, mental toughness, mood state, and sports anxiety) and aerobic capacity (VO₂Max) in Malaysian sub-elite athletes. A cross-sectional design was utilised, encompassing 228 participants from the Malaysian National Sports School system. Psychological assessments were conducted concurrently with the 20-meter shuttle run test to evaluate VO2Max. Multiple regression analysis indicated a non-significant overall model (F(11, 216) = 1.597, p = .101), explaining 7.5% of the variation in VO2Max values. Two variables were identified as statistically significant: emotional intelligence in regulating others' emotions (negatively correlated) and mood state confusion (positively correlated). Other psychological qualities, such as anxiety dimensions, mental toughness, and emotional self-regulation, were not significant predictors. These findings underscore the complex and perhaps paradoxical links between psychological and physiological performance indicators in sub-elite athletes. The research highlights the significance of comprehensive performance models that encompass both mental and physical aspects and proposes that specific psychological therapies might enhance endurance performance in competitive environments.